2011
DOI: 10.1111/j.1600-0501.2011.02254.x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic evaluation of early loaded narrow diameter implants – 1‐year follow‐up

Abstract: Treatment with OsseoSpeed TX 3.0S implants is a safe and predictable option in the anterior region where physical space is limited. Minimal marginal bone loss was observed during the first year follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
63
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(73 citation statements)
references
References 37 publications
10
63
0
Order By: Relevance
“…The mean recorded marginal bone loss was 0,73±0,33mm and 0,88±1,13mm for test and control group respectively and was similar to that reported for the same implant system used in other reports, albeit in different contexts. Results from the present investigation are consistent with findings from other studies that reported on marginal bone loss around Osseospeed implants: De Bruyn (26) described a mean value for marginal bone loss at 3-year follow up of 0,4±1,5mm, Galindo-Moreno (27) reported a mean value of 0,065±1,01mm at 1-year follow up, Bilham (21) reported a mean value of 0,95±0,18mm at 3-year follow-up, Chang (28) found a mean marginal bone loss of 0,45±1,15mm at 5-year follow up.…”
Section: Discussionsupporting
confidence: 82%
“…The mean recorded marginal bone loss was 0,73±0,33mm and 0,88±1,13mm for test and control group respectively and was similar to that reported for the same implant system used in other reports, albeit in different contexts. Results from the present investigation are consistent with findings from other studies that reported on marginal bone loss around Osseospeed implants: De Bruyn (26) described a mean value for marginal bone loss at 3-year follow up of 0,4±1,5mm, Galindo-Moreno (27) reported a mean value of 0,065±1,01mm at 1-year follow up, Bilham (21) reported a mean value of 0,95±0,18mm at 3-year follow-up, Chang (28) found a mean marginal bone loss of 0,45±1,15mm at 5-year follow up.…”
Section: Discussionsupporting
confidence: 82%
“…Regarding the type of edentulism, three studies included only totally edentulous individuals (16,21,24), five studies included both partially and totally edentulous patients (13,19,22,30,31), seven studies included partially edentulous cases (12,18,20,26-29), and six studies included only patients with a single missing tooth (13-15,23,25,32). …”
Section: Resultsmentioning
confidence: 99%
“…Nine studies used a single-step surgical protocol (12-15,20-22,26,27), five studies used a two-step protocol (17,19,24,25,31), two studies included both single and two-step surgical protocols (18,30), and three studies performed surgery involving the raising of a full-thickness flap without offering further details (16,28,29). Only three studies presented results comparing implants placed with a flapless technique versus the raising of a full-thickness flap (15,23,29). …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations